Utilizing Intraoperative Navigated 3D Color Doppler Ultrasound in Glioma Surgery - Saß, Benjamin; Pojskic, Mirza; Zivkovic, Darko; Carl, Barbara; Nimsky, Christopher; Bopp, Miriam H. A. (Frontiers in Oncology, 2021)
Background: In glioma surgery the patient’s outcome is dramatically influenced by the extent of resection and residual tumor volume. To facilitate safe resection neuronavigational systems are routinely used. However, due to brain shift accuracy decreases with the course of the surgery. Intraoperative ultrasound has proved to provide excellent live imaging, which may be integrated into the navigational procedure. Here we describe the visualization of vascular landmarks and their shift during tumor resection using intraoperative navigated 3D color Doppler ultrasound (3D iUS color Doppler). Methods: 6 patients suffering from glial tumors located in the temporal lobe were included in this study. Intraoperative computed tomography was used for registration. Datasets of 3D iUS color Doppler were generated before dural opening and after tumor resection and the vascular tree was segmented manually. In each dataset, 1 – 4 landmarks were identified, compared to the preoperative MRI, and the Euclidean distance was calculated. Results: Pre-resectional mean Euclidean distance of the marked points was 4.1 ± 1.3 mm (mean ± SD), ranging from 2.6 mm to 6.0 mm. Post-resectional mean Euclidean distance was 4.7. ± 1.0 mm, ranging from 2.9 to 6.0 mm. Conclusion: 3D iUS color Doppler allows estimation of brain shift intraoperatively, thus increasing patient safety. Future implementation of the reconstructed vessel tree into the navigational set-up might allow navigational updating with further consecutive increasement of accuracy.